Discovery of an exosite on the SOCS2-SH2 domain that enhances SH2 binding to phosphorylated ligands - Edmond M. Linossi (Nature Portfolio, 2021)
SOCS2 is a key regulator of growth hormone and cytokine signaling, which recognizes phosphotyrosine (pTyr)-modified targets via a central SH2 domain. Here, the authors discover and characterize an exosite on this SH2 domain that can bind a non-phosphorylated peptide to enhance SOCS2:pTyr affinity.